Methods of improving accounts payable and receivable - Lyovina V. A. (Relevant lines of scientific research: theory and practice, 2016)
In article the question of calculation with suppliers and buyers is considered, recommendations about improvement of calculations with partners are made. Relevance of this subject is that development and improvement of accounting of calculations with partners exerts a direct impact on financial result of the organization, through regulation of receivables and payables.
Keywords: дебиторская задолженность; кредиторская задолженность; расчеты с поставщиками; расчеты с покупателями; Calculations with suppliers; calculations with buyers; receivables; accounts payable